⇒ 2x^{2} + x = 4

Dividing both sides of the equation by 2, we get

⇒ x^{2} +\( \dfrac{x}{2}\) = 2

Now on adding \(( \dfrac{1}{4})^2\)^{ }to both sides of the equation, we get,

⇒ \( (x)^2 + 2 × x ×\) \( \dfrac{1}{4}\) + \( ( \dfrac{1}{4})^2\) = 2 + \( ( \dfrac{1}{4})^2\)

⇒ \( (x + \dfrac{1}{4})^2 = \dfrac{33}{16}\)

⇒ \( x + \dfrac{1}{4} = ±\dfrac{\sqrt{33}}{4}\)

⇒ \( x = ±\dfrac{\sqrt{33}}{4}-\dfrac{1}{4}\)

⇒ \( x = \dfrac{\sqrt{33-1}}{4}or\;\dfrac{-\sqrt{33-1}}{4}\)

Answered by Abhisek | 1 year agoA natural number when increased by 12 equals 160 times its reciprocal. Find the number.

Find a natural number whose square diminished by 84 is equal to thrice of 8 more than the given number.

The numerator of a fraction is 3 less than the denominator. If 2 is added to both the numerator and the denominator, then the sum of the new fraction and the original fraction is \( \dfrac{29}{20}\) Find the original fraction.

The sum of the squares of two consecutive even numbers is 340. Find the numbers.

The sum of the squares of two consecutive multiple of 7 is 637. Find the multiples.